2020
DOI: 10.1007/s40268-020-00293-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Pharmacokinetic Study of Fixed-Dose Combinations of Ibuprofen and Acetaminophen in Healthy Adult and Adolescent Populations

Abstract: Introduction A fixed-dose combination (FDC) of ibuprofen and acetaminophen has been developed that provides greater analgesic efficacy than either agent alone at the same doses without increasing the risk for adverse events. Methods We report three clinical phase I studies designed to assess the pharmacokinetics (PK) of the FDC of ibuprofen/ acetaminophen 250/500 mg (administered as two tablets of ibuprofen 125 mg/acetaminophen 250 mg) in comparison with its individual components administered alone or together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
6
0
2
Order By: Relevance
“…However, FDC IBU/APAP 200 mg/500 mg and FDC IBU/APAP 300 mg/500 mg were significant versus ibuprofen 400 mg for SPRID [4] 0-2 (p < 0.05). Similar patterns were seen for time-weighted SPID [4] and SPID [11] scores over the same time intervals (data not shown).…”
Section: Efficacysupporting
confidence: 77%
See 1 more Smart Citation
“…However, FDC IBU/APAP 200 mg/500 mg and FDC IBU/APAP 300 mg/500 mg were significant versus ibuprofen 400 mg for SPRID [4] 0-2 (p < 0.05). Similar patterns were seen for time-weighted SPID [4] and SPID [11] scores over the same time intervals (data not shown).…”
Section: Efficacysupporting
confidence: 77%
“…Ibuprofen and acetaminophen do not share metabolic pathways, which diminishes the likelihood of drug–drug interactions [ 8 , 9 ]. Pharmacokinetic studies have demonstrated a lack of drug–drug interactions between ibuprofen and acetaminophen [ 6 , 10 , 11 ]. Ibuprofen and acetaminophen also have different side-effect profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Five of the trials enrolled otherwise healthy adults; two trials included participants that were healthy adolescents. In all, the trials comprised three phase 1 PK trials (2 single-dose trials in adults; 1 single-dose trial in adolescents) [21], 3 dental pain model efficacy trials (a phase 2 single-dose proof-of-concept [26]), a phase 3 single-dose, and a phase 3 multiple-dose trial [20], and 1 single-dose phase 3 trial using an endotoxin-induced fever model. Details of the individual studies included in this pooled safety analysis are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the individual studies included in this pooled safety analysis are provided in Table 1. In all studies, patients were monitored for AEs throughout the study and AEs were reported through 14 days after administration of the last dose of study drug regardless of causality [21,26]. In the dental pain model studies, patients were permitted to take immediate-release tramadol or codeine phosphate at any time during the study as rescue medication, but were encouraged to wait at least 1 hour [26] after study medication administration before doing so.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation